Identifying Potentially Preventable Reasons Nurses Intend to Leave a Job. (11th February 2022) - Taylor-Clark, Tanekkia M.; Swiger, Pauline A.; Anusiewicz, Colleen V.; Loan, Lori A.; Olds, Danielle M.; Breckenridge-Sproat, Sara T.; Raju, Dheeraj; Patrician, Patricia A.
Abstract : Supplemental digital content is available in the text. Abstract : OBJECTIVE: The aim of this study was to describe the relationships between intent to leave, reasons nurses intend to leave, and the nursing work environment in military hospitals. BACKGROUND: Intention to leave is a precursor of nurse turnover. The reasons nurses intend to leave may be influenced by leader interventions and potentially preventable. METHODS: This descriptive, correlational secondary analysis included 724 nurse survey responses from 23 US Army hospitals. Bivariate correlations and predictive modeling techniques were used. RESULTS: Forty-nine percent of nurses indicated they intended to leave, 44% for potentially preventable reasons. Dissatisfaction with management and the nursing work environment were the top potentially preventable reasons to leave. Nurses who intended to leave for potentially preventable reasons scored aspects of the nursing work environment significantly lower than those intending to leave for nonpreventable reasons. CONCLUSIONS: Identifying potentially preventable reasons in conjunction with intent to leave can provide leaders opportunities to intervene and influence turnover intention.